NÍVEIS DE COBERTURA VEGETAL DO SOLO NA CULTURA DO TOMATE IRRIGADO - Hupalo, Marcelo Ferreira (2013)
Tomato is the most important economic vegetable in Brazil. The state of Parana is a significant fresh market tomato grower, and the Reserva city is the largest grower in this state. The tomato crop is important to family based farm because it contribute to income and employ generation, however it has a high financial cost and highly demand of handling practices and cultivation. Among farming practices stands irrigation, which can influence the crop production and fruit quality. For environmental issues, thinking about conservation of soil and water, the irrigation practice should be performed properly. The no-tillage system is established in erosion control, reduction of soil temperature range and contamination reduction in water sources in grain crops. In vegetable crops, especially in tomato crop, this must be better studied. The aim of this study was to assess consumption of irrigation water, soil temperature range, quality of the harvested product, yield and efficiency of water use in the production of fresh market tomatoes in the Campos Gerais region according to the level of cover crop. The treatments were quantities of dry matter on the soil: T1 (no dry matter on the soil); T2 (3.09 Mg ha-1 of dry matter); T3 (5.03 Mg ha-1 of dry matter); T4 (7.17 Mg ha-1 of dry matter) and T5 (9.20 Mg ha-1 of dry matter). There was significant effect of different levels of dry matter on the irrigation water consumption, where the increase of dry matter promoted the reduction of irrigation depth (mm) applied ranging 17 to 30%. No-tillage system promoted, on average, savings of 20% of irrigation water applied when compared to conventional production system. The maximum and miminum temperatures and soil temperature range decreased with the increase of dry matter on the soil. The increase in dry matter on the soil promoted high yield of total marketable fruits and high yield of fruits from 3A and 1A classes. Moreover this decreased the proportion of non-marketable fruits with disruption and blossom-end rot. The maximum and minimum temperatures and the thermal amplitude of the soil were reduced with the increase of dry matter on ground. The increase of dry matter on the soil promoted greater total marketable fruit yield and maximum fruit yield of 3A and 1A classes. Furthermore, reduced the proportion of unmarketable fruits with blossom end rot and cracking. The increase of dry matter on the soil caused greater yield and total marketable fruit yield of 05 to 15%.